Pelatihan Pemanfaatan Sampah Plastik sebagai Material Produk Hiasan bagi Lulusan SMA di Kota Tangerang - Ali Ramadhan; Lelo Lelo; Ridwan Rasyid (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
Nowadays, waste is one of the environmental problems, because plastic waste is known to have a long life to decompose in the soil. Ornamental products are one of the products that have good value and can be placed freely. This activity aims to develop knowledge in terms of making decorative products using plastic waste. Participants are high school graduates in Tangerang. By using training methods, ornamental products can be developed using basic plastic waste materials that have gone through the pre-processing stage. The training stage includes presentation, material selection, design, material processing, review, and display. The implementation of this activity, it was found that the use of plastic waste which is used as a base material for ornamental products can provide additional knowledge to high school graduates as well as increase the ability to practice in making design works. Participants had the opportunity to have income from the sale of the product design of the waste processing. How to cite:Ramadhan, A., Lelo, L., Rasyid, R. (2020). Pelatihan Pemanfaatan Sampah Plastik sebagai Material Produk Hiasan bagi Lulusan SMA di Kota Tangerang. Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 5(1), 1-17.DOI: https://doi.org/10.26905/abdimas.v5i1.3083